Entre photos, graphias, imaginários e memórias: a (re) invenção do ser professor - Brandão, Cláudia Mariza Mattos (2012)
This study is part of the Research Lines Written Culture, Languages and Learning, based on the studies undertaken by the Group for Studies and Research on Imaginary, Memory and Education (GEPIEM). This is a qualitative research with a socio-phenomenological methodology guided by the principles of convergence of Gilbert Durand. The investigation seeks to glimpse the mythical universe of representations of teaching, demonstrating the ability of photography to express symbols introjected, giving visibility to the imaginary founding of the subjects. It examines the multiple meanings that move this universe of representations (which are to Gilbert Durand presentification their archetypal inheritances), from photo-graphias produced by training and trained teachers, attendees of courses by the researcher in different cities of the state of Rio Grande do Sul, between 2007 and 2010. These images were obtained in response to the provocation "Being Teacher is..." taking as his motto the continuation of the sentence, through photographs. Thus, the photographic language, in this thesis, is characterized as an exercise of introspection activator of creative imagination, as Gaston Bachelard proposes. The inventory and the subsequent empirical analysis of capital allowed the identification of the recurrent symbolic core, determined by significant homologies (repetitions) of symbols expressed by photographic schemes. They were arranged in a chronic form of visual narrative and through the exercise of photo analysis - a methodology for convergence proved significant repetitions present in the universe of symbols of teaching, expressed from different people and places. By weighting on the correspondence between the archetypal imagery speeches that make up the interstices of the research you can access other ways to say and say. In general, this mode of expression allows bringing symbolic "answers", like those in this thesis led to Prometheus, Hermes and Narcissus myths as directors of the universe of representations of teaching. Therefore, this work is revealing the photo of the imaginary presentification referring to the symbolic universe is interwoven Teacher. The research contributes to the construction of these different perspectives and knowledge on the subject, aiming to promote the recognition of substrates of social attitudes, reflected in attitudes and behaviors, with the instance of the symbolic and archaic revealing roots that bind us to the path of anthropological being.